Actions of intravenous injections of AVP and oxytocin on plasma ACTH, GH, insulin and glucagon concentrations in goats. (10th November 2013) - Roh, Sang‐gun; Koiwa, Kohta; Sato, Katsuyoshi; Ohtani, Yoshihisa; Takahashi, Tatsuyuki; Katoh, Kazuo
Abstract This study was conducted to investigate the arginine‐vasopressin (AVP)‐ and oxytocin‐induced changes in plasma adrenocorticotropic hormone (ACTH), growth hormone (GH), insulin and glucagon levels and their metabolite concentrations in goats. In this study, five goats were intravenously injected with either AVP (0.3 nmol/kg body weight (BW)) or oxytocin (0.7 IU/kg BW). AVP injection significantly increased ACTH and GH secretions compared to controls, although insulin and glucagon concentrations were not altered. The incremental areas (ICAs) of the ACTH and GH concentrations were higher in the AVP group than in the saline group. Oxytocin injections increased insulin and glucagon secretions, while ACTH level was not altered. GH levels became elevated 30 min after the oxytocin injection. The ICAs of insulin and glucagon after oxytocin was injected were higher than those of the control. Results indicate that AVP is a potent stimulant of ACTH and GH secretions, while oxytocin uses different pathways to regulate insulin and glucagon secretions in goats.